“Hurray for Reflection!” – A Handbook for Connecting Reflective Practice and Cooperative Learning - Olah, Katalin (Autonomy and Responsibility Journal of Educational Sciences, 2023)
“Hurray for Reflection!” – A Handbook for Connecting Reflective Practice and Cooperative Learning Jacobs, M. G., Lie, A. & Tama, S. M. (2022). Cooperative learning through a cooperative lens. Bristol CT: Equinox Publishing.